علم الدلالة / المفهوم والعلائق - بغورة ياسين (Université de M'sila, 2020)
إن الاهتمام باللغة حتمية اجتماعية ،كونها ذخيرة الأمة، وركيزتها التي تبني عليها حضارتها ومجدها، وهي وسيلة تواصلية تحقق تفاعل المجتمع واستمراريته، واللغة مجموعة من المستويات المتكاملة التي تحقق باجتماعها المعاني المرادة، ولا تتحق هذه الفائدة إلا بتوفر المستوى الصوتي والصرفي والنحوي ثم يأتي المستوى الدلالي الذي يتوقف عند المعنى، لذلك تستوقفنا هذه الدراسة عند هذا المستوى، لما يحمله من أهمية بالغة في الدرس اللغوي، محاولين الإجابة عن إشكالية متعلقة بالمفهوم والعلائق. interesting in language is a social necessity since it is considered not only as the linguistic provision of any nation and the pillar on which it builds its own civilization and glory, but also the means of communication that ensures interaction and continuity of society. In fact, the language is a set of levels that complement each other and ensure by their meeting the desired meanings, but it is impossible to reach this goal only by the union of the phonological, morphological and grammatical levels, then that of the semantics in which is formed. meaning. This is why this study tries to take an interest in this last level, in particular to answer to the problematic relating to the concepts and relations
Keywords: الدلالة ; اللغة ; المست ; يات ; المعنى ; significan ; significance ; langage ; levels ; meaning